Issue on measuring the light speed in vacuum - Chaban Vasyl (Lviv Politechnic Publishing House, 2021)
Based on the proposed differential equations of the interaction of the electric signal with the gravitational field, the observed phenomena are known as the gravitational lens and the Shapiro effect are investigated. The deflection of a light ray in the field of the Sun is simulated. It is shown that a moving photon undergoes in the gravitational field not only a transverse action, which causes a curvature of the trajectory but also a longitudinal one, implementing the acceleration-braking processes. As a result, the instability of the speed of light in a vacuum was revealed.
Keywords: Differential equations; gravitational lens; the light signal in gravity; speed of light in vacuum; quasi-constant